Turbocharging small size engine to increase engine output: an assessment of turbocharger study field - Herzwan, H. M.; Azri, Alias; R., Mamat (IOP Publishing, 2019)
In recent years, engine downsizing becomes popular in modern vehicles since rising demands for less consuming vehicle and more stringent emission regulations. Along with this trend, turbocharging also gains popularity as a method to increase the output of small size engine hence enables it to produce comparable output to bigger displacement engine. In this paper, recent turbocharger studies in three major area that are heat transfer studies, flow studies and mechanical studies are reviewed. In heat transfer studies, the findings from experimental and modelling of heat transfer are presented. For flow studies, the reviews are separated to the different part of the turbocharger and method of study. While for mechanical studies in turbocharger, the mechanical losses in turbocharger was reviewed. At the end of this review, the area of interest for the next study will be concluded.